REFLECTION OF POTATO VARIETIES TO MIDSEASON WATER LIMITATION (Mongolian Journal of Agricultural Sciences, 2015)
Climate change is expected to exacerbate drought events throughout the world, resulting in large-scale ecosystem alteration and failure of drought-sensitive crops. In addition, periods of drought vary from year to year both in severity and length, making it difficult for plants to adapt to more severe conditions. Many modern varieties of potatoes are considered to be drought-sensitive. Potato growing in the agro-ecology environment of the country is believed as little risky for dry farming, but weather change during the last years’ requests to be reassessed the circumstances. Especially, the coincidence of hot weather frequency and rainfall shortage in July with potato tuber bulking causes the downed harvest. This trial conducted to reveal potato plant tolerant to water stress, including 6 more common varieties. The varieties were grown in non-stressed and 15 days water limitation conditions. There was revealed that potato growing in the non-stressed condition provided to harvest 6.0 t/ha or 15,6per cent higher yield than with water limitation treatment.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 60-62